PEMANFAATAN BAKTERI PELARUT FOSFAT UNTUK MENINGKATKAN PRODUKTIVITAS KUDZU TROPIKA (Pueraria phaseoloides Benth.) - Roni, N. G. K; Witariadi, N.M.; Candraasih K., N.N; Siti, N. W (Pastura; Vol 3 No 1, 2014)
Phosphorus (P) is one of the essential nutrients for plants that availability is strongly influenced by soil pH. In acid soils, most of the P is given will form insoluble compounds and is not available to plants. Phosphate solubilizing bacteria is a soil microorganism that can improve the provision ofP in acid soils. The study aimed to determine the effect of Phosphate solubilizing bacteria on the productivity of tropical kudzu was conducted using a completely randomized design with four treatments ie without isolate (I0), standard isolate (I1), isolate B.80.1649-1 (I2) and isolate B.80.1649-8 (I3), each treatment was repeated four times. The results showed that both isolates were isolated and selection were able to increase the length of the plants, number of leaves, shoot dry weight, root dry weight, shoot P content,  N uptake, P uptake, and production of crude protein of tropical kudzu (Pueraria phaseoloides Benth.). The ability of isolates B.80.1649-1 higher than isolates B.80.1649-8, and comparable with standard isolate.
Keywords: Bacteria Solvent Phosphate, phosphorus, tropical kudzu